2019
DOI: 10.1159/000494932
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Ankyrin 1 Enhances Ovalbumin-Induced Acute Allergic Inflammation in Murine Models

Abstract: Background: Transient receptor potential ankyrin 1 (TRPA1) is an ion channel known to mediate nociception and neurogenic inflammation, and to be activated by reactive oxygen and nitrogen species (ROS and RNS) produced at the sites of inflammation. Because neurogenic inflammation as well as the release of ROS and RNS are typical features of early stages of allergic responses, we hypothesized that TRPA1 may be involved in triggering and/or amplifying allergic inflammation. Objective: This study aims at exploring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It has also been reported that IL-13 up-regulates TRPV1 in the bronchial epithelial cells in the lung of asthmatic BALB/c mice 54 . However, treatment directed at TRPV1 significantly alleviated IL-4, IL-5, and IL-13 level in a chronic asthma murine model, while conversely TRPA1 promoted OVA-induced IL-4 production during acute allergic lung inflammation 55 , 56 . These findings will guide us in further identifying the relationship and mechanisms of TG2 interaction with TRPA1, TRPV1 and IL-6 & IL-4, IL-13 using TG2 null mice and in vitro cultured cell.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that IL-13 up-regulates TRPV1 in the bronchial epithelial cells in the lung of asthmatic BALB/c mice 54 . However, treatment directed at TRPV1 significantly alleviated IL-4, IL-5, and IL-13 level in a chronic asthma murine model, while conversely TRPA1 promoted OVA-induced IL-4 production during acute allergic lung inflammation 55 , 56 . These findings will guide us in further identifying the relationship and mechanisms of TG2 interaction with TRPA1, TRPV1 and IL-6 & IL-4, IL-13 using TG2 null mice and in vitro cultured cell.…”
Section: Discussionmentioning
confidence: 93%
“…Wild‐type and MKP‐1 deficient C57BL/6 mice 6 originating from the R. Bravo laboratory at Bristol‐Myers Squibb Pharmaceutical Research Institute (Princeton, NJ, USA) were used in the experimental model of allergy. Mice were cared under standard conditions and anaesthetized as previously described 7 . The study was performed in accordance with the EU directive on the protection of animals used for scientific purposes (Directive 2010/63/EU) and upon approval of National Animal Experiment Board.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were cared under standard conditions and anaesthetized as previously described. 7 The study was performed in accordance with the EU directive on the protection of animals used for scientific purposes (Directive 2010/63/ EU) and upon approval of National Animal Experiment Board. The animal experiments were conducted in the preclinical facility of Tampere University, Tampere, Finland, and the laboratory analyses were performed in the laboratory of the Immunopharmacology Research Group, Tampere University, Tampere, Finland, in 2021.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation